PENDAMPINGAN IMPLEMENTASI SISTEM PENGELOLAAN REKAM MEDIS BAGIAN FILING SECARA SENTRALISASI - Endang Sri Dewi Hastuti Suryandari; Gunawan .; Achmad Zani Pitoyo (Politeknik Kesehatan Kemenkes malang, 2019)
Medical record storage on the shelf filing is to simplify and speed up the retrieval of the documents at any time needed. The purpose of these activities was to make the health officers in Community Health Centre (CHC) understood and could implemented the centralization medical record filing system in CHC. Mentoring activities for implementation of centralization medical record filing system in Kendalkerep CHC Malang, could improved the knowledge of the CHC’s officers about the centralization medical record filing system using SNF (Straight Numeric Filing) method. The result of this mentoring activity showed the medical record’s officers of the Kendalkerep CHC Malang could implemented the centralization medical record filing system using the SNF (Straight Numeric Filing) properly. 90% of the CHC’s officers stated satisfied following the mentoring activity and 10% stated very satisfied. The Head of the Kendalkerep CHC Malang should validate and establish the Decree Letter of medical record management and SOP (Standard Operating Procedure) of the medical record management system as a guideline for all the activity at medical record unit.